Electron spin resonance and magnetic phase transitions in manganite perovskite La₀.₇₈Sr₀.₂₂MnO₃ synthesized by the solid-phase reaction method - Kalmykova, T.; Vakula, A.; Nedukh, S.; Tarapov, S.; Belous, A.; Krivoruchko, V.; Suhov, R. (Functional Materials, 2018)
Magnetic properties of nanopowder of perovskite manganite doped with strontium La₀.₇₈Sr₀.₂₂MnO₃ are studied using electron paramagnetic resonance method. Analysis of the experiments in the temperature range T = 77-290 K shows that this structure is a typical nanostructure only at T < 100 K. In the remaining temperature region, the structure is in the superparamagnetic and noncollinear superparamagnetic magnetic state.